A Comparison of Patient and Surgeon Expectations of Spine Surgical Outcomes. Issue 3 (April 2021) - Aoude, Ahmed; Litowski, Madison; Aldebeyan, Sultan; Fisher, Charles; Hall, Hamilton; Manson, Neil; Bailey, Christopher S.; Ahn, Henry; Abraham, Edward; Nataraj, Andrew; Paquet, Jerome; Stratton, Alexandra; et al.
Study Design: Ambispective cohort study. Objective: Limited data exists comparing surgeon and patient expectations of outcome following spine surgery. The objective of this study was to elicit whether any differences exist between patient and surgeon expectations for common spine surgeries. Methods: Ten common age-appropriate clinical scenarios were generated and sent to Canadian spine surgeons to determine surgeon expectations for standard spine surgeries. Patients in the Canadian Spine Outcomes and Research Network (CSORN) registry matching the clinical scenarios were identified. Aggregated patient expectations were compared with surgeon responses for each scenario. A χ 2 analysis was then completed to determine discrepancies between surgeon and patient expectations for each scenario. Results: A total of 51 Canadian spine surgeons completed the survey on surgical expectations. A total of 919 patients from multiple centers were identified within the CSORN database that matched the clinical scenarios. Our results demonstrated that patients tend to be more optimistic about the expected outcomes of surgery compared with the treating surgeon. The majority of patients in all clinical scenarios anticipated improvement in back or neck pain after surgery, which differed from surgeon expectations. Results also highlighted the effect of patient age on both patient and surgeon expectations. Discrepancies between patient and surgeon expectations were higher for older patients. Conclusion: We present data on patient and surgeon expectations for spine surgeries and show that differences exist particularly concerning the improvement of neck or back pain. Patient age plays a role in the agreement between the treating physicians and patients in regard to surgical expectations. The reasons for the discrepancies remain unclear.